A study of non-alcoholic fatty liver disease in patients with type 2 diabetes mellitus and its correlation with cardiovascular risk - Giri, Richa; Kumar, Vinit; Kumar, Vinay; Agarwal, Saurabh (International Journal of Advances in Medicine, 2022)
Background: NAFLD (non-alcoholic fatty liver disease) encompasses a variety of disorders of lipid metabolism ranging from NAFL, NASH to cirrhosis and rarely HCC. A great deal of evidence suggests that the metabolic syndrome predicts incident cardiovascular disease (CVD), so it is possible to hypothesize that NAFLD patients might portend a greater CVD risk and that NAFLD itself might confer a CVD risk above that associated with individual metabolic syndrome risk factors. Methods: 55 T2DM patients were included in current study conducted from August 2019 to September 2021 for assessment of NAFLD using USG abdomen, NAFLD fibrosis score and FIBROSCAN. ASCVD score was used for correlation between CVD risk and NAFLD. Results: Out of 55 patients 42 (76.4%) were having fatty liver based on USG abdomen while 13 (23.4%) patients were having no fatty liver. As far as steatosis is concerned mean CAP (dB/m) was 245±50.89 out of which 24 (43.6%) were having no or minimal steatosis (S0), while 31 (56.4%) were having significant steatosis with 11 (20%), 9 (16.4%) and 11 (20%) having S1, S2 and S3 grade of steatosis respectively. 15 patients out of 55 were of F0 grade while 19 (34.5%), 9 (16.4%), 7 (12.7%) and 5 (9.1%) were of grade F1, F2, F3 and F4 respectively. There was a positive statistically significant (p≤0.001) association of ASCVD risk score with NAFLD fibrosis score and fibroscan: E (KPa). Conclusions: Our study found that the prevalence of NAFLD was quite higher in patients with T2DM based on both USG abdomen (76.4%) and transient elastography (steatosis-56.4% and fibrosis-65.5%) and a statistically significant association between fibrosis and ASCVD score with higher fibrosis associated with higher 10 years ASCVD score.